Association of epicardial adipose tissue and coronary artery calcium score in patients with atrial fibrillation. (19th May 2022) - Fernandes, S; Ladeiras-Lopes, R; Cruz, I; Silva, G; Silva, M; Queiros, P; Diaz, S; Barros, A; Saraiva, F; Faria, R; Almeida, J; Fonseca, P; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Both coronary artery calcium (CAC) and epicardial adipose tissue (EAT) had been implicated in coronary artery disease (CAD) and risk of future adverse cardiovascular events. There are scarce data regarding the assessment and association of EAT volume and CAC score (CACS) in atrial fibrillation (AF) patients. Purpose: To assess the association between EAT volume and the presence and severity of CAC in patients with AF. Methods: Retrospective and single-centre study including consecutive patients with AF undergoing contrast-enhanced cardiac computed tomography for catheter ablation planning, from 2017 to 2019. Patients with known history of CAD and moderate to severe valvular heart disease were excluded. Baseline clinical and demographical data were collected, as well as their cardiovascular risk, based on the SCORE (Systematic Coronary Risk Evaluation) system and cardiovascular risk categories. We assessed CACS (Agatston method) and EAT volume and analysed their association. EAT was defined as the adipose tissue accumulated between the visceral pericardium and the myocardium and was semi-automatically reconstructed by manually tracing the pericardium. Patients were split into three groups according to CACS: 0, 1-99 and ≥100. A logistic regression (LR) analysis was performed to explore the relationship between EAT volume and the presence of CAC (CACS>0), adjusted for age, gender, obesity, diabetes mellitus and hypertension. Results: A total of 354 patients were included, with a mean age of 56 ± 12 years, 66% male and 21% with persistent AF. A CHA2DS2-VASc score ≥2 was present in 130 (37%) patients and most patients had low to moderate cardiovascular risk (n=213, 82%). More than half of the patients had a CACS>0 (n=185, 52%), of which 63 patients (18%) had a CACS≥100. The mean EAT volume was 79 ± 39 ml. There was a significant association between EAT volume and the presence of CAC: CACS=0 69 ± 34 ml vs CACS 1-99 84 ± 38 ml vs CACS ≥100 95 ± 45 ml (p<0.001) (Fig. 1). After covariate adjustment (LR model R2 = 0.373, p <0.0001), the presence of CAC was not associated with EAT volume (OR 1.00, 95%CI 1.00 - 1.01, p=0.2) or obesity, and only with higher age, male gender, hypertension and diabetes mellitus (Fig. 2). Conclusion: In our cohort of patients with AF undergoing catheter ablation we observed an association between EAT and CACS. Nevertheless, EAT volume was not an independent predictor of CACS and only the classical cardiovascular risk factors remained significant.